In vitro Evaluation of the Location of Cholesteryl Ester Deposits on Monthly Replacement Silicone Hydrogel Contact Lens Materials - Qiao H (Dove Medical Press, 2020)
Han Qiao,1 Doerte Luensmann,1 Miriam Heynen,1 Elizabeth Drolle,1 Lakshman N Subbaraman,1 Charles Scales,2 Donald Riederer,2 Zohra Fadli,2 Lyndon Jones1,3 1Centre for Ocular Research & Education (CORE), School of Optometry & Vision Science, University of Waterloo, Waterloo, ON, Canada; 2Johnson & Johnson Vision Care, Inc, Jacksonville, FL, USA; 3Centre for Eye & Vision Research (CEVR), Hong Kong, People’s Republic of ChinaCorrespondence: Doerte Luensmann Email dluensma@uwaterloo.caPurpose: The deposition profile of cholesteryl ester on the surface and throughout the matrix of silicone hydrogel contact lens (CL) materials was determined under conditions that mimic a daily wear regimen.Methods: In this in vitro study, four SiHy CL materials (senofilcon C, lotrafilcon B, comfilcon A and samfilcon A) were incubated in an artificial tear solution (ATS) for up to 30 days. CL incubation was alternated between the ATS (16 hours) and a multipurpose care regimen (8 hours). The ATS included fluorescently tagged cholesteryl ester (5-cholesten-3ß-ol 6-[(7-nitro-2-1,3-benzoxadiazol-4-yl)amino]caproate; CE-NBD) and confocal laser scanning microscopy visualized the distribution of the lipid through the CLs.Results: The distribution of CE-NBD was homogenous from the anterior to posterior surface in senofilcon C and comfilcon A, at all time points. For lotrafilcon B and samfilcon A, CE-NBD localization was heterogeneous, with greater amounts on the surfaces on Day 1 and Day 14 compared to the lens matrix; however, differences in concentration between the surface and bulk diminished by Day 30.Conclusion: The distribution of the non-polar lipid CE-NBD varied with lens material chemistry. While some lens materials deposited the lipid primarily on the surface after 16 hours of exposure, all materials exhibited a homogenous distribution after one month.Keywords: lipid distribution, silicone hydrogel contact lenses, cholesteryl ester, artificial tear solution